Development of an integrated reactor model package for optimizing the operating modes of the sulfur production unit - Batyr Orazbayev; Nazgul Kurbangaliyeva; Kulman Orazbayeva; Ainur Zhumadillayeva; Xiaoguang Yue (Scientific Reports)
Abstract Complex technological systems in oil refining and other industries, consisting of numerous interconnected units, are often characterized by the uncertainty of initial information required for modeling and optimizing their operating modes. This study addresses the issue of uncertainty in the development of models for such technological systems with fuzzy input, operational, and output parameters, which remain relevant yet underexplored and unresolved. The paper proposes a concept for developing a model package of interconnected units for technologically fuzzy systems and describes the implementation algorithm of the proposed concept. Based on this algorithm, hybrid models of interconnected reactors in the sulfur production unit at the Atyrau refinery were developed, consisting of statistical, fuzzy, and linguistic models. These models allow the determination of the sulfur volumes produced in the reactors and their fuzzy quality indicators depending on the reactors’ operating modes. The developed models of interconnected reactors, including the Claus thermal reactor and Cold Bed Absorption, are combined into a single model package according to the sulfur production process and the technological scheme of the research object. The resulting model package enables systematic modeling of reactor systems and the selection of optimal operating modes. For this purpose, a software suite was created to simulate various operating modes of the reactor system on a computer to optimize their operation. The results of systematic modeling and optimization of the sulfur production unit demonstrate the advantages of the proposed approach compared to known methods.